2007
DOI: 10.1007/s00418-007-0298-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the novel protein PTPIP51 in rat liver: an immunohistochemical study

Abstract: Expression of the novel protein tyrosine phosphatase interacting protein 51 (PTPIP51) was investigated on mRNA and protein level in the liver of adult Wistar rats. The presence of PTPIP51 mRNA was detected by Northern blotting. Immunostaining showed expression of PTPIP51 protein in distinct non-parenchymal cells. These cells were identified as Kupffer cells, stellate cells and natural killer cells by detection of cell-specific antigens. Whereas most endothelial cells lining large vessels reacted positive to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…PTPIP51 lacking this N-terminal sequence shows a cytosolic localization and is unable to induce programmed cell death. This is in accordance with previous observations (Stenzinger et al 2007). Pathre and colleagues (2001) reported neurite outgrowth in the chicken retina to be regulated by a molecular system including a cleaved form of PTP1B as an integrated component.…”
Section: Retinal Developmentsupporting
confidence: 94%
“…PTPIP51 lacking this N-terminal sequence shows a cytosolic localization and is unable to induce programmed cell death. This is in accordance with previous observations (Stenzinger et al 2007). Pathre and colleagues (2001) reported neurite outgrowth in the chicken retina to be regulated by a molecular system including a cleaved form of PTP1B as an integrated component.…”
Section: Retinal Developmentsupporting
confidence: 94%
“…These findings may be explained by putative isoforms or splicing variants expressed in different tissues that lack this N‐terminal sequence, which is mandatory for the execution of apoptosis [4, 8]. This hypothesis is supported by the fact that PTPIP51 was not found to be exclusively restricted to mitochondria but was present at the cellular membrane and to a lower extent in the cytosol of malignant keratinocytes [7, 8, 36]. The intracellular localization may also be explained by an in vivo interaction with PTP1B or Src‐kinases.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that expression of the the novel tyrosine phosphatase interacting protein 51 (PTPIP51), a protein which is present in diVerent mammalian species and tissues (e.g., Stenzinger et al 2007) and which has been suggested in in vitro studies to be involved in diVerentiation and programmed cell death, is present in ganglion cell layers and photoreceptor cells and is downregulated in cultured postnatal rat retinal explants by CNTF (Roger et al 2007). To elucidate a possible role of PTPIP51 in eye development, Maerker et al (2008) studied the expression of PTPIP51 during the organogenesis of the mouse eye using RT-PCR and in situ hybridization, immunohistochemistry and Western blotting.…”
Section: Developmental Studiesmentioning
confidence: 98%